2003
DOI: 10.1038/sj.ijo.0802411
|View full text |Cite|
|
Sign up to set email alerts
|

Almonds vs complex carbohydrates in a weight reduction program

Abstract: OBJECTIVE:To evaluate the effect of an almond-enriched (high monounsaturated fat, MUFA) or complex carbohydrate-enriched (high carbohydrate) formula-based low-calorie diet (LCD) on anthropometric, body composition and metabolic parameters in a weight reduction program. DESIGN: A randomized, prospective 24-week trial in a free-living population evaluating two distinct macronutrient interventions on obesity and metabolic syndrome-related parameters during weight reduction. SUBJECTS: In total, 65 overweight and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
243
4
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 195 publications
(262 citation statements)
references
References 55 publications
11
243
4
4
Order By: Relevance
“…Despite an additional 300kcal to the dietary energy intake, no significant intake in calories was reported in the food diaries for any group nor was there any significant change in BMI in the intervention groups suggesting energy compensation by subjects; this compensation effect has been reported in previous studies with almond snacks [38]. It has been reported previously that nut intake increases satiety, which may explain the reduction in calories consumed from non-almond foods [39].…”
Section: Discussionmentioning
confidence: 73%
“…Despite an additional 300kcal to the dietary energy intake, no significant intake in calories was reported in the food diaries for any group nor was there any significant change in BMI in the intervention groups suggesting energy compensation by subjects; this compensation effect has been reported in previous studies with almond snacks [38]. It has been reported previously that nut intake increases satiety, which may explain the reduction in calories consumed from non-almond foods [39].…”
Section: Discussionmentioning
confidence: 73%
“…7 The ability of a physician to adapt downward on the number and dosing of medications used to treat type 2 diabetes can be profound when carbohydrate intake is minimal in the context of a hypocaloric diet. 6 Over the past several decades, we have noted that many patients have stated that they believe that a weight-loss diet that is higher in one or more of the macronutrients may work best for them for weight management (eg, low-fat, high-carbohydrate diet; high-protein, low-carbohydrate diet), which may reflect their unique level of success or failure with prior dieting experiences. Sacks et al randomly assigned 811 overweight adults to one of four diets (targeted percentages of energy derived from fat, protein, and carbohydrates in the four diets were 20%, 15%, and 65%; 20%, 25%, and 55%; 40%, 15%, and 45%; and 40%, 25%, and 35%) for two years and found that diets with varying amounts of carbohydrate, protein, and fat are equally successful in promoting clinically significant weight loss and maintenance over two years, thus refuting prior studies showing that a high-protein, low-carbohydrate diet can facilitate greater weight loss over a six-month initial period.…”
Section: One Size Does Not Fit Allmentioning
confidence: 99%
“…Thus, interventions including a variety of methods with follow-up visits that are tailored to meet the client's desires and health goals are more likely to promote successful weight loss and maintenance. In light of our experience with using nuts in overweight and obese patients seeking weight loss, 6,20 a review of the current evidence to date and discussion of the potential mechanisms by which nuts may influence body weight are featured in the following section.…”
Section: Weight Maintenancementioning
confidence: 99%
See 2 more Smart Citations